Study of the utilization of non-timber forest vegetation by local society at PT. Wira Karya Sakti Sungai Tapa conservation area - Jambi - MULYATI RAHAYU; SITI SUSIARTI; Y. PURWANTO (Biodiversitas Journal of Biological Diversity, 2007)
Forest exploitation especially for the material wood/timber has giving influence to condition environment and the society who lives around the forest. Therefore in this time, the research for non timber forest products is being an interest fot the researchers from many sciences. There is not than 100 plants species useful of non timber producer had known from the research which conducted in PT. Wira Karya Sakti conservation forest area in Sungai Tapa-Jambi. Two of them (Alstonia scholaris R.Br. and Scorodocarpus borneensis (Baillon) Jack) are included in a list of endangered species plants in Indonesia.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Non Timber Forest Products, Jambi